A fresh look into background electrolyte selection for capillary electrophoresis‐laser induced fluorescence of peptides and proteins. Issue 18 (29th May 2019) - Morani, Marco; Taverna, Myriam; Mai, Thanh Duc
Abstract: This study reports a reinvestigation of background electrolyte selection strategy for performance improvement in CE‐LIF of peptides and proteins. This strategy is based on the employment of high concentrations of organic species in BGE possessing high buffer capacity and low specific conductivity in order to ensure excellent stacking preconcentration and separation resolution of fluorescently tagged peptides and proteins. Unlike universal UV detection, the use of such BGEs at high concentrations does not lead to degradation of LIF detection signals at the working excitation and emission wavelengths. At the same buffer ionic strength, pH and electric field, an "inorganic‐species‐free" BGE (or ISF BGE) for CE‐LIF of fluorescently labeled beta amyloid peptide Aβ 1–42 (a model analyte) offered a signal intensity and peak efficiency at least three‐times higher than those obtained with a conventional BGE normally used for CE‐LIF, while producing an electric current twice lower. Good peak performance (in terms of height and shape) was maintained when using ISF BGEs even with samples prepared in high‐conductivity phosphate buffer saline matrix. The advantageous features of such BGEs used at high concentrations over conventional ones in terms of high separation resolution, improved signal intensities, tuning of EOF magnitudes and minimization of protein adsorption on an uncoated fused silica capillary are demonstrated using Alexa‐488‐labelled trypsin inhibitor. Such BGE selection approach was applied for investigation of separation performance for CE‐LIF of ovalbumin labelled with different fluorophores.